Estrés materno y vínculo de apego entre madre - hijo prematuro en Hospital Regional Docente de Trujillo - Cancho Rodríguez, Liz Isaura (2019)
This quantitative research study, of correlational descriptive type, was performed in mothers with preterm infants hospitalized in the Neonatal Intensive Care Unit of the Regional Teaching Hospital of Trujillo, in order to determine the relationship between maternal stress level and attachment bond. The data collection was done through the application of two instruments: Stress Level Scale and Attachment Matching List. The information obtained was processed in statistical tables and graphs according to the objectives. The analysis of the relationship of the variables under study was performed using the Gamma statistical test. The following results were found: the 87.5% of the mothers had a high stress level and 12.5% had a low stress level. Regarding the bond of attachment, 75% had an acceptable attachment bond, while 22.5% had a deteriorated bond attachment and 2.5% had an optimal bond attachment. There is a significant statistical relationship between both variables. (p= 0,049)